Evaluation of a river classification system as a conservation measure in the management of Atlantic salmon in Insular Newfoundland. (9th May 2013) - Veinott, G.; Cochrane, N.; Dempson, J. B.
Abstract In an effort to address the decline in abundance of Atlantic salmon, Salmo salar L., in insular Newfoundland rivers, resource managers introduced a River Classification System (RCS) in 1999 to assist in the management and conservation of the resource. The RCS set daily and seasonal bag limits in the recreational fishery on a river by river basis. An analysis of the catch and effort data before and after the implementation of the RCS showed an overall decline in the number of retained salmon after the implementation of the RCS, but no change in overall effort. Upon closer examination, it was found that retention increased on Class I rivers, which had the highest allowed retention, but declined on the other class rivers. On one particular river (Harry's River), which alternated classifications from 2007 to 2010, it was found that exploitation rates increased as allowed retention increased. Newfoundland salmon anglers appear to be retention anglers and therefore the RCS was an effective tool for diverting catch and effort to specific rivers by changing retention limits.